Business Registration in Nepal - Shrestha, Ramesh (PYC Nepal Journal of Management, 2010)
Industrial Enterprises Act, 1992 and Industrial Policy, 2010 require registration for all kinds of business in Nepal. Micro and traditional cottage industries, however, may be registered within one month of their operations. Despite the requirement, businessmen and entrepreneurs are reluctant to get their enterprises registered. This essay examines the causes of such reluctance. A questionnaire survey of 350 entrepreneurs and other data suggest majority of them are unaware of such requirement and those who are aware find the requirement difficult and complex.